Legal Consequences of the Concept of Implied Consent in terms of the Cases of Legal Right of Pre-emption, Mesne Profits and Semen of Intervension - Nagehan Kırkbeşoğlu (İstanbul Hukuk Mecmuası)
There is a limit in the provisions of the legislation regarding the use and disposal of shareholders and stakeholders in joint and shared ownership. Indeed, according to Article 693 of the Turkish Civil Code No 4721, “each of the stakeholders can benefit from and use the shared property to the extent that it is compatible with the rights of the others”. According to TCC Art 689/I, “stakeholders may, by unanimous agreement among themselves, make regulations different from the provisions of the law on matters related to utilization, use and management.” A similar provision also exists in joint ownership. Indeed, according to TCC 702/II, “unless there is a contrary provision in the law or contract, the shareholders must decide unanimously for both management and disposition transactions”. The situation becomes even more complicated when stakeholders/shareholders allocate an area that the other stakeholder/partner can use more or less. Because the law does not regulate concept that emerges as the de facto division phenomenon in practice. In every case where it is accepted that implicit consent has been given, the condition of prohibition of usufruct in terms of retaliation is required, and the use of the legal right of pre-emption and the semen of intervension is prevented. Therefore, it is necessary to say that the burden of declaration is placed on the stakeholder/shareholder who is considered to have given implicit consent to the de facto use. In this study, the issue of how the concept of implicit consent, which causes these deprivations of rights, how it should be formed and proven, has been examined separately under the title of each right and finally under the title of concept of implicit consent with a general evaluation.